Environmental Ethics and Sustainability During Pandemic Era - Nassereldeen, Kabbashi A.; Aisha, Hassan Abdalla Hashim; Elfatih, Abdelsalam Abdullahi; Galal, Fatima A. (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
The relationship between human beings and environment is not new, it started with the creation of mankind and his availability on earth, the communication between them was at a high level of trust, but with wrong doings of human on earth and for his selfishness, the earth started to change her face, as such many disasters happened as earthquake, flooding, and the worse was the pandemic diseases. Water, solid and air are the main components for environment, and misbalance in them may result to sort of crises, but the serious one among the three environmental components is the air, without it all livings will be affected, and this is what happened at this serious COVID-19 pandemic and lock down to the people’s life on earth. This paper focused on why such pandemic crises happened on earth, who is responsible for it, and why it may continue to happen and how can we sustain our living on earth with ethics, values, and norms.